A Hermeneutic Approach to Pain: Gadamer on Pain, Finitude, and Recovery - Alexander Crist (University of Calgary, 2018)
While philosophical hermeneutics has often been criticized for not engaging issues concerning the body and human finitude, Gadamer’s ‘Defense of Pain’ in his final public academic appearance is an underappreciated hermeneutic contribution to the way in which we experience and respond to the physical and existential demands of pain. In light of his criticism, that the modern medical community is occupied with the utter eradication of pain, Gadamer is concerned with the consequences of such a sensibility which does not appear to focus on developing and fostering the patients’ own capacities and participation in the process of their own convalescence. For Gadamer, the patients’ active participation in the recovery (verwinden) from pain is an opportunity to experience the joys of recovery and to engage in their own vibrant rhythm of health. Yet more than this, pain is an opportunity to return to an existential and hermeneutic truth about one’s own finitude. Through reflections on the newborn’s cry at birth (Geburtsschrei) and the forgetfulness of our own mortality, we find in Gadamer’s presentation an intriguing account of pain as a deeply embodied and hermeneutic experience that furthers interpretation and understanding of our own intimate relationship with birth, death, and life.